2018
DOI: 10.1001/jamapsychiatry.2018.0252
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Rostral Anterior Cingulate Cortex Theta Activity in Relation to Symptom Improvement in Depression

Abstract: clinicaltrials.gov Identifier: NCT01407094.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 58 publications
8
131
1
2
Order By: Relevance
“…However, in the field of functional biomarkers, e.g. in neurophysiological research, several large studies have revealed meaningful patterns of ANS and CNS activity (Arns et al, 2015;Olbrich et al, 2016;Pizzagalli et al, 2018) that may inform the diagnostic process and the choice of treatment. The presented case now adds a possible marker for ERP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the field of functional biomarkers, e.g. in neurophysiological research, several large studies have revealed meaningful patterns of ANS and CNS activity (Arns et al, 2015;Olbrich et al, 2016;Pizzagalli et al, 2018) that may inform the diagnostic process and the choice of treatment. The presented case now adds a possible marker for ERP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more sophisticated analyses, such as theta-gamma phase-amplitude coupling (Sun et al, 2015;Noda et al, 2017), or dynamic causal modelling to determine changes in effective connectivity between brain regions (Lu et al, 2012;Harding et al, 2015;Breakspear, 2017), may reveal the effects of the intervention. For example, theta connectivity localised to the anterior cingulate cortex has been identified as a predictor of antidepressant response to treatment courses using transcranial magnetic stimulation (Narushima et al, 2010;Bailey et al, 2018), and sertraline (Pizzagalli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, probably the best supported candidate for a neuroimaging response biomarker is pgACC, with its increased activity being a predictor of good clinical response consistently shown over the past 20 years (e.g. [10,22,23]) and supported by meta-analyses and systematic reviews [19, 20••]. PgACC plays a crucial role in the development of depressive symptoms and antidepressant response due to its central position between the circuits responsible for a quick automatic response to emotionally salient stimuli and prefrontal regions exerting cognitive control over them.…”
Section: Pregenual Anterior Cingulate Cortex (Pgacc): a General Respomentioning
confidence: 99%